European catfish (Silurus glanis) movements and diet ecology in a newly established population in the Tagus drainage - Ferreira, Marco Alexandre Morgado Frade (2019)
Tese de mestrado, Biologia da Conservação, Universidade de Lisboa, Faculdade de Ciências, 2019